Nagori ashwagandha: A viable alternative crop for arid ecosystem - Saran, Parmeshwar L; Das, Manish (Indian Horticulture, 2023)
India is a vast country with a wide range of agro-climatic conditions. Medicinal crops like ashwagandha are very sensitive to soil and climatic conditions. Region specific cultivation has the potential to provide benefits in ter ms of environmental protection, conservation of species and improved raw drug quality. India is bestowed with a lot of potential to produce medicinal crops in particular agro-ecological regions because the country has diverse agro-climatic regions. Therefore, region specific cultivation of ashwagandha for better performance under sandy plains of central to western Rajasthan will be targeted. Keeping in view the above facts, ashwagandha elite (DTWr-1) should be cultivated in particular agro-climatic pockets to boost the productivity and quality of raw drug. At the same time, farmers can earn more than ` 2.5 to 3.00 Lakhs per hectare within 180-185 days under Chahi condition of sandy plains of central to western Rajasthan.